Non-pharmacological management of fever in otherwise healthy children - Watts, Robin; Robertson, J. (University of Adelaide, 2012)
Background: Fever is a common childhood problem faced in both hospital and community settings. In many cases the fever is associated with mild to moderate self-limiting illnesses. There has been a rapid increase in antipyretic use as the means of managing or treating this adaptive physiological response to infection. The use of alternative means of caring for a febrile child could minimise the amount of antipyretics administered to children and thereby reduce the potential risks. Objective: The objective of this systematic review was to establish what non-pharmacological practices are effective in managing fever in children, three months to 12 years of age, who are otherwise healthy. Inclusion criteria: Interventions for inclusion were physiological e.g. maintenance of hydration and rest, and external cooling, either direct e.g. sponging, clothing, or environmental e.g. fans, ambient temperature. Outcomes of interest were effect on fever, increase in comfort, decrease in parental anxiety and reduction in unnecessary use of health services. Search strategy: The search sought English, Spanish, Portuguese, Mandarin and Italian language studies, published 2001-2011 in 12 major databases. Critical appraisal, data extraction and data synthesis:Critical appraisal of and data extraction from eligible studies were undertaken using standardised tools developed by the Joanna Briggs Institute. As statistical pooling of data was precluded, the findings are presented in narrative form.Results: Twelve randomised controlled trials were included, involving 986 children in total. Only one intervention identified in the review protocol – direct external cooling measures – was addressed by the studies. Eleven studies included sponging as an intervention while one also included clothing (unwrapping). No studies investigated physiological interventions, (e.g. hydration or rest), or environmental cooling measures, (e.g. fans or ambient temperature) as separate interventions. Three of these interventions (encouragement of fluid intake, rest and fans) were reported as part of the standard care provided to participants in several studies or were controlled in the study (ambient temperature). Only two of the four outcomes identified in the review protocol were examined (effect on fever (all 12 studies) and patient comfort). Although tepid sponging alone resulted in an immediate decrease in temperature, this response was of short duration, with antipyretics or antipyretics plus sponging having a more lasting effect. In addition, the observed levels of discomfort of the sponged children were higher than the other groups. For both measures, this effect was not statistically significant in every case.Conclusion: The care of a febrile child needs to be individualised, based on current knowledge of the effectiveness and risks of interventions. The administration of antipyretics should be minimised, used selectively and with caution, even in otherwise healthy children. The results of this systematic review support previous findings that routine tepid sponging does not have an overall beneficial effect. However measures such as encouraging fluid intake and unwrapping the child should be encouraged. Implications for practice: The two foci of care should be the child and the parents/primary caregiver. For the child, care should aim to support the body’s physiological responses i.e. maintain hydration, minimise use of antipyretics. Support the parents to reduce anxiety e.g. by involving them in care and providing appropriate education, particularly in respect to correct dosages of antipyretics. Implications for research: Given the now well demonstrated discomfort engendered by tepid sponging, its use in treating febrile children is no longer advocated and does not warrant further research. However aspects of other non-pharmacological interventions have not been so well researched e.g. parental response to advice on fluid intake and appropriate clothing.